Digitalisasi Produk UMKM Masyarakat Kelurahan Karangtalun Guna Meningkatkan Pemasaran Dengan Menggunakan Metode Penta Helix - Mochamad Rifqi Hananto; If Bambang Sulistyono (IKRA-ITH ABDIMAS, 2023)
Industrial Revolution 4.0 has a significant impact on the development of information technology.Advances in technology and modernization have influenced various sectors, one of which is theeconomic sector. Micro and Small and Medium Enterprises (MSMEs) in the home industry isrequired to be able to always innovate marketing and products produced in order to remaincompetitive in the changing times. Product digitalization is one of the efforts of MSME actors located in Karangtalun Village, North Cilacap District, Cilacap Regency, Central Java to improvemarketing aspects. In this case, students as intellectuals have the obligation to run the Tri Dharmaof Higher Education, one of which is community service. Through this KKN activity, studentsprovide assistance to SMEs in Karangtalun Village to optimize the marketing of digital-basedproducts. In this activity, we also use the Penta Helix method to optimize the expected results bysynergy through the village government, students as academics, SBIs, home UMKM actors, MSMEcommunities and Karangtarunau villages, and digital media. The method used is through aqualitative approach preceded by a survey to inventory the problems of MSME actors, thencontinued by conducting direct socialization. The results of this activity are the process of obtainingPIRT permits, packaging updates, making product photos, and making Urban village websites thatfocus on the MSME sector. This activity affects the mindset of MSME actors to be able to developtheir products for the better.